사회적경제기본법(안)의 사회적경제 및 사회적경제조직의 정의에 관한 연구 - 안수정; 조성호 (원광법학, 39(3), 2023)
사회적경제기본법(안)은 21대국회에서 5차례 발의되었다. 사회적경제라함은 내부적으로 조직의 민주성과 자율성을 지니고 이를 통해 외부적으로 여러 가치와 목적을 추구하는 경제활동의 속성을 지닌 것으로 보고 있다. 그러나 21대국회에 발의된 입법안들을 보면 사회적경제에 대한 정의규정에서 대내적으로 호혜협력, 호혜와 연대 등의 내용을 포함하고 있지만 그 주안점은 내부적 활동이나 조직보다는 사회적가치의 실현과 같은 외부적 활동에 중점을 둔 형식을 취하고 있다. 사회적경제조직의 정의에 대해서도 본래 의미에서는 내부적 자율적 운영과 민주적 의사결정구조를 지닌 조직만이 사회적경제조직이어야 함에도 불구하고 의원들의 입법안에서는 사회적경제조직을 사회적가치를 추구하면서 재화 및 용역의 구매･생산･판매･소비 등 영업활동을 하는 사업조직 등으로 정의함으로써 사실상 내부적 자율성과 민주적 의사결정구조에 관한 요건은 언급하지 않고 있다. 그리고 이에 따라 의원들이 제시한 사회적경제기본법(안)은 기존의 사회적기업 육성법과 차별화를 부각하지 못하였고 입법화가 진행되지 못하고 있다. 따라서 사회적경제기본법(안)이 본래 의미의 사회적경제 및 사회적경제조직에 부합하도록 내부적 자율성과 민주적 의사결정구조에 관한 내용을 정의규정에 삽입하여야 하며 또한 사회적경제조직의 요건으로 별도로 내부적 자율성과 민주적 의사결정구조에 관한 사항을 입법안에 조문으로 명시하는 것이 필요하다. 이러한 정의규정의 보완 및 요건의 추가를 통해 본래 의미의 사회적경제가 법안에 반영되고 입법화가 원활히 이루어질 것으로 기대한다. The Social Economy Basic Law (draft) has been proposed five times in the 21st National Assembly. The social economy is considered to have the attributes of economic activities that have organizational democracy and autonomy internally and pursue various values and purposes externally. However, according to the legislative bills proposed in the 21st National Assembly, the definition of social economy includes contents such as reciprocal cooperation, reciprocity and solidarity internally, but the main focus is on external activities such as the realization of social values rather than internal activities or organizations. As for the definition of a social economy organization, although it should be an organization with internal autonomous operation and democratic decision-making structure, the lawmakers' bill defines a social economy organization as a business organization that engages in business activities such as purchasing, producing, selling, and consuming goods and services while pursuing social values, and in fact does not mention the requirements for internal autonomy and democratic decision-making structure. As a result, the Social Economy Basic Act proposed by lawmakers has not been able to differentiate itself from the existing Social Enterprise Development Act and has not been enacted. Therefore, it is necessary to insert the contents of internal autonomy and democratic decision-making structure into the definition regulations so that the Basic Social Economy Act (Draft) is in line with the original meaning of social economy and social economy organizations, and to specify the contents of internal autonomy and democratic decision-making structure separately as requirements for social economy organizations in the legislation. It is expected that the original meaning of social economy will be reflected in the bill and the legislation will be smoothly implemented through the supplementation of the definition and the addition of requirements. KCI Citation Count: 0